2006
DOI: 10.4049/jimmunol.177.7.4636
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of IL-2 Induced IL-10 Production as a Principle of Phase-Specific Immunotherapy

Abstract: Leishmania donovani, a protozoan parasite, inflicts a fatal disease, visceral leishmaniasis. The suppression of antileishmanial T cell responses that characterizes the disease was proposed to be due to deficiency of a T cell growth factor, IL-2. We demonstrate that during the first week after L. donovani infection, IL-2 induces IL-10 that suppresses the host-protective functions of T cells 14 days after infection. The observed suppression is concurrent with increased CD4+glucocorticoid-induced TNF receptor+ T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 32 publications
0
39
0
1
Order By: Relevance
“…The infection-induced expansion of MDSCs, which suppressed the immune response during active disease, could be rendered inefficient for suppression by treatment with glycyrrhizic acid, which inhibits arginase I and Cox-2. Since one of the immunopathological consequences of visceral leishmaniasis is antigen-specific suppression of T cell responses (35), a gradual expansion of MDSCs in L. donovani-infected BALB/c mice is consistent with immunosuppression to establish the infection by favoring the survival of the parasites. SLA-immunized BALB/c mice resisted the expansion of these MDSCs to direct the host's immune system toward a self-healing phenotype at a 1 ϫ 10 6 dilution of parasites or lower (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The infection-induced expansion of MDSCs, which suppressed the immune response during active disease, could be rendered inefficient for suppression by treatment with glycyrrhizic acid, which inhibits arginase I and Cox-2. Since one of the immunopathological consequences of visceral leishmaniasis is antigen-specific suppression of T cell responses (35), a gradual expansion of MDSCs in L. donovani-infected BALB/c mice is consistent with immunosuppression to establish the infection by favoring the survival of the parasites. SLA-immunized BALB/c mice resisted the expansion of these MDSCs to direct the host's immune system toward a self-healing phenotype at a 1 ϫ 10 6 dilution of parasites or lower (see Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, one of the disease-promoting T cells in L. major infection is Treg cells, as the reduction in parasite burden has been correlated with reduced number of Treg cells (24)(25)(26)(27)(28). To explore the prophylactic role for TLR2-TLR6 heterodimer, we primed BALB/c mice with fixed L. major and BPPcysMPEG, followed by challenge infection with L. major.…”
Section: Discussionmentioning
confidence: 99%
“…Treg cells promote Leishmania survival and growth in a susceptible host, as the numbers of Treg cells increase in progressive infection (24)(25)(26)(27)(28), but depletion of Treg cells reduces the disease (26,47). As BPPcysMPEG reduced L. major infection in BALB/c mice (Fig.…”
Section: Bppcysmpeg Reduced Treg Cells In Cocultures With Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in L. donovani infection IL-10 is increasingly being designated as the suppressive cytokine produced from a population of regulatory T cells (8); expansion and/or activation of these cells might be able to suppress both Th1 and Th2 cells. Reportedly, in L. donovani infection, an IL-10-rich splenic environment is created during the effector phase of the antileishmanial immune response by IL-10-secreting CD25 ϩ suppressor T cells that inhibit the activation of naive T cells (8). Interestingly, it has been recently shown that IFN-␥ produced by tumor-specific CD8 ϩ CTL cells inhibits the generation and/or activation of suppressive regulatory T cells (35).…”
Section: Discussionmentioning
confidence: 99%